2004
DOI: 10.1074/jbc.m313366200
|View full text |Cite
|
Sign up to set email alerts
|

κ Opioid Receptor Interacts with Na+/H+-exchanger Regulatory Factor-1/Ezrin-Radixin-Moesin-binding Phosphoprotein-50 (NHERF-1/EBP50) to Stimulate Na+/H+ Exchange Independent of Gi/Go Proteins

Abstract: We previously showed that Na ؉ /H ؉ -exchanger regulatory factor-1/Ezrin-radixin-moesin-binding phosphoprotein-50 (NHERF-1/EBP50) co-immunoprecipitated with the human opioid receptor (hKOR) and that its overexpression blocked the agonist U50,488H-induced hKOR down-regulation by enhancing recycling. Here, we show that glutathione S-transferase (GST)-hKOR Ctail interacted with purified NHERF-1/EBP50, whereas GST or GST-C-tails of or ␦ opioid receptors did not. GST-hKOR C-tail The opioid receptor (KOR)1 is one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…However, DOPr trafficking was not modulated by either a mitogen-activated protein kinase (MAPK) inhibitor or a protein kinase C (PKC) inhibitor (Bie et al, 2010). This latter study also implicated recruitment of a scaffolding protein Na + /H + exchange regulatory factor (NHERF)-1, which was shown to be involved in the sorting of internalized b-2ARs and KOPrs to recycling pathways for resensitization (Huang et al, 2004;Weinman et al, 2006;Hanyaloglu and von Zastrow, 2008). Finally, the appearance of increased functional DOPr induced by chronic morphine was blocked by an inhibitor of protein transport from the ER to the Golgi apparatus (Bie et al, 2010), suggesting that morphine modulates the maturation and sorting of newly synthesized DOPrs.…”
Section: Confoundsmentioning
confidence: 79%
See 1 more Smart Citation
“…However, DOPr trafficking was not modulated by either a mitogen-activated protein kinase (MAPK) inhibitor or a protein kinase C (PKC) inhibitor (Bie et al, 2010). This latter study also implicated recruitment of a scaffolding protein Na + /H + exchange regulatory factor (NHERF)-1, which was shown to be involved in the sorting of internalized b-2ARs and KOPrs to recycling pathways for resensitization (Huang et al, 2004;Weinman et al, 2006;Hanyaloglu and von Zastrow, 2008). Finally, the appearance of increased functional DOPr induced by chronic morphine was blocked by an inhibitor of protein transport from the ER to the Golgi apparatus (Bie et al, 2010), suggesting that morphine modulates the maturation and sorting of newly synthesized DOPrs.…”
Section: Confoundsmentioning
confidence: 79%
“…M6a overexpression was shown to redirect DOPr to the recycling path (Liang et al, 2008), but it is not yet known whether it has this same effect at endogenous expression levels. NHERF also interacts with DOPr, although with much lower affinity than KOPr (Huang et al, 2004). However, in brainstem neurons, increases in extracellular levels of NGF induce NHERF expression and drive its interaction with DOPr, redirecting receptors from their intracellular stores to the membrane (Bie et al, 2010).…”
Section: D-opioid Receptor Pharmacologymentioning
confidence: 99%
“…[7][8][9]. We have demonstrated that activation of opioid receptors stimulates Na ϩ , H ϩ -exchanger 3 activity via NHERF-1/EBP-50 independent of pertussis toxin-sensitive G proteins (10). In this study, we identified proteins interacting with the human opioid receptor (hKOR) by yeast two-hybrid screening of a human brain cDNA library using the cytoplasmic tail (C-tail) as the bait.…”
mentioning
confidence: 99%
“…After receptor activation, both ␣ and ␤␥ subunits of G proteins recruit downstream signaling effectors to inhibit adenylyl cyclase and voltage-gated Ca 2ϩ channels and to stimulate G proteinactivated inwardly rectifying K ϩ channels, mitogen-activated protein kinase, and phospholipase C␤ (for a review, see Law et al, 2000b). In addition, activation of the KOR regulates Na ϩ ,H ϩ -exchanger 3 via interaction with Ezrin-radixin-moesin-binding phosphoprotein-50/Na ϩ ,H ϩ -exchanger regulatory factor-1 (EBP50/NHERF-1) (Huang et al, 2004).…”
mentioning
confidence: 99%